Dermatological and Dermoscopic Baselines in BRCA Mutation Carriers - Paolino, Giovanni; Pampena, Riccardo; Di Nicola, Matteo Riccardo; Longo, Caterina; Rognone, Alessia; Zambelli, Stefania; Bianchini, Giampaolo; Mercuri, Santo Raffaele (Frontiers in Medicine, 2022)
Breast cancer-associated gene 1 and 2 (BRCA1 and BRCA2) are tumor suppressor genes encoding a large protein that is involved in many essential biological processes. BRCA mutated patients show an increased risk to develop several malignancies, including cutaneous malignancies, although inconsistently across multiple studies. We carried out an observational study on the main dermatological and dermoscopic aspects in a population of patients with BRCA1/2 mutations, in order to identify the main clinical and dermoscopical features in this class of patients. A total of 52 patients with BRCA mutations were included in the current analysis. Clinical, dermoscopical and pathological data were obtained during the dermatologic visits. Out of the entire cohort, 67.3% patients showed brown hairs , 63.5% of patients showed brown eyes, with phototype III as the most frequent phototype (69.2%). A total of 2.017 melanocytic lesions in all patients were analyzed; specifically,40 patients (76.9%) showed a total number of nevi >10, while regarding the main observed dermoscopic features, a prevalence of reticular pattern in 63% of cases was observed, followed by mixed pattern in 19.2% of cases. Regarding the cutaneous examination, eruptive angiomas (eCAs) were the main dermatologic manifestations in 46.2% of patients. Out of 52 patients and during a follow-up of 24 months one patient developed an in situ melanoma. Interestingly, none of the patients with eCAs showed a TN>10, highlighting an inverse correlation. To date, there is insufficient evidence to warrant increased surveillance in patients with BRCA mutations or with a positive family history for BRCA mutations, in the absence of standard cutaneous risk factors. Further studies with larger samples of patients are needed to better investigate dermatological and dermatoscopic features in BRCA mutation carriers.